Metastasis of breast cancer to major duodenal papilla - Bastos, Tiago (2017)
Metastasis is an infrequent cause of tumor involvement of the major duodenal papilla and of cholestasis. We report a case of obstructive jaundice due to a metastatic breast carcinoma to the major duodenal papilla, and assess curative and palliative treatment that interventional endoscopy can offer.